Hollow-Core Photonic Crystal Fibers for Surface-Enhanced Raman Scattering Probes - Xuan Yang; Chao Shi; Rebecca Newhouse; Jin Z. Zhang; Claire Gu (International Journal of Optics)
Photonic crystal fiber (PCF) sensors based on surface-enhanced Raman scattering (SERS) have become increasingly attractive in chemical and biological detections due to the molecular specificity, high sensitivity, and flexibility. In this paper, we review the development of PCF SERS sensors with emphasis on our recent work on SERS sensors utilizing hollow-core photonic crystal fibers (HCPCFs). Specifically, we discuss and compare various HCPCF SERS sensors, including the liquid-filled HCPCF and liquid-core photonic crystal fibers (LCPCFs). We experimentally demonstrate and theoretically analyze the high sensitivity of the HCPCF SERS sensors. Various molecules including Rhodamine B, Rhodamine 6G, human insulin, and tryptophan have been tested to show the excellent performance of these fiber sensors.